ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KEDELAI MENGGUNAKAN METODE EOQ PADA PABRIK TEMPE KARYA MANDIRI DI KOTA PEKANBARU - Z Iqbal rafsanjani Moh; Samsir Samsir; Marpaung Jonnes M. Rio (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted with the aim of knowing the optimal quantityof soybean raw material purchases at Karya Mandiri factory, the frequency ofpurchasing raw materials, the amount of safety stock, determining the reorderpoint and the total cost of the soybean raw material inventory. using theEconomic Order Quantity method. The object of this research is the KaryaMandiri factory in Pekanbaru City. Sources of data obtained by interviewobservation and documentation. This type of research used by the author isdescriptive research using a quantitative approach. The results of the analysisshow that if the factory applies the Economic Order Quantity method in 2022 forthe optimal purchase of soybean raw materials, the difference in savings in thetotal cost of raw materials for soybean 2022 is IDR 354,281. Based on the resultsthat have been analyzed using the Economic Order Quantity method, the factoryshould use this method in determining optimal raw material purchases so that theKarya Mandiri factory can minimize the total inventory costs incurred for thecoming period. Keywords: Economic Order Quantity Method, Raw material inventory